Successful hearing preservation and improved subjective sound quality with the flexible 28-mm electrode array - Calvino, Miryam; Sánchez-Cuadrado, Isabel; Muñoz, Elena; Gavilán, Javier; Lassaletta, Luis (Frontiers in Audiology and Otology, 2024)
Introduction: Flexible electrode arrays have shown to be an effective solution to ensure atraumatic insertion. However, flexible full-length electrodes are not suited for patients with smaller cochleae. Therefore, this study aimed to evaluate short-term and medium-term hearing preservation (HP) in patients with low-frequency residual hearing (LFRH) who were implanted with a flexible 28-mm electrode array and who did not meet the indication criteria for electricacoustic stimulation (EAS).Methods: HP was determined based on the pure-tone audiogram of the implanted ear. A bisyllable sentence test was used to assess speech perception in quiet and in noise. The hearing implant sound quality index (HISQUI19) evaluated self-reported hearing quality. The tests were conducted pre-and postoperatively, at first fitting, and at 1, 3, 6, and 12 months after first fitting.Results: At 12 months post first fitting, 2 patients had complete HP; 4 patients had partial HP. Speech perception scores improved in all patients of the study. The mean scores on the bisyllable sentence test in noise significantly increased from 30% preoperatively to 62% 6 months post first-fitting and to 68% 12 months post first-fitting. The mean score of the HISQUI19 improved from 40.56 (poor) preoperatively to 72.56 (moderate) 1 month post firstfitting and to 90.29 (good) 12 months post first-fitting.The 28-mm flexible electrode array facilitates atraumatic surgery and HP and results in improved speech perception and subjective sound quality scores.